1971
DOI: 10.1159/000192800
|View full text |Cite
|
Sign up to set email alerts
|

Die arteriellen Blutgaspartialdrücke und ihre Beziehungen zu Alter und anthropometrischen Grössen

Abstract: The partial pressures of oxygen and carbon dioxide of the arterial blood were examined under strictly standardized conditions. The relationship of PaO2 to age was found as YR = -0.40 age + 96.2 and PaCO2 to age as YR = 0.03 age + 36.0. Furthermore, a correlation between PaCO2 and PaO2 could be calculated as YR = -0.073 PaO2 + 43.0. An estimation of PaO2 by biometrical data is given: YR= -0.39 age – 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
3
4

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
1
5
3
4
Order By: Relevance
“…Using these norms, we attempted to minimize the num ber of false pathological findings. Lower normal P a0 2 values reported in the liter ature are obtained from capillary blood [Hertle et al, 1971]. The effect of age on P a02 and (A-a)02 [Sorbini et al, 1968;Raine and Bishop, 1963;Hertle et al, 1971;Diament et al, 1969] could not be demonstrated in our patients.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Using these norms, we attempted to minimize the num ber of false pathological findings. Lower normal P a0 2 values reported in the liter ature are obtained from capillary blood [Hertle et al, 1971]. The effect of age on P a02 and (A-a)02 [Sorbini et al, 1968;Raine and Bishop, 1963;Hertle et al, 1971;Diament et al, 1969] could not be demonstrated in our patients.…”
Section: Discussioncontrasting
confidence: 70%
“…Lower normal P a0 2 values reported in the liter ature are obtained from capillary blood [Hertle et al, 1971]. The effect of age on P a02 and (A-a)02 [Sorbini et al, 1968;Raine and Bishop, 1963;Hertle et al, 1971;Diament et al, 1969] could not be demonstrated in our patients. lebavy/Fabián/Henzlová/Belán To our knowledge, pulmonary gas ex change in patients with stable IHD in rela tion to the degree of involvement of the coronary system and left ventricular func tion has not been reported in the literature.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…2). Hypercapnia (Pa,CO 2 w43 mmHg) [20] at peak exercise was present in 7/23 of the non-FL patients and in 21/29 of the FL patients (pv0.005). In FL patients, there was a significant fall in Pa,O 2 from rest to peak exercise (pv0.05), whereas in non-FL patients the Pa,O 2 did not change significantly.…”
Section: Resultsmentioning
confidence: 94%
“…Statistisch auffällige oder gesicherte Korrelatio nen finden sich weiterhin zum FEVi.o und zu Grössen des respiratorischen Gasaustausches, nämlich Pa02 und AaDc>2. Da diese Grössen aber ebenfalls Beziehungen zu Alter und anthropometrischen Daten aufweisen [7], wurde, um Scheinkorrelationen zu vermeiden [9] [8].…”
Section: Diskussionunclassified